PEDAGOGICAL ASPECTS OF FORMING PROFESSIONAL COMPETENCE OF FUTURE TEACHERS - Turdiqulova Luiza Zayniddinovna (Bright Mind Publishing, 2025)
The article presents information on the pedagogical aspects of the formation of professional competence of future teachers.
Keywords: Competence, professional competence, competent approach, pedagogical personality, motivation, education, pedagogical technology.